Moral narratives, civic trust, and electoral legitimacy in local Indonesian democracy - Akhmad Muzadi; Fitriyah; Muhammad Adnan; Wijayanto (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Moral narratives are defined as publicly endorsed narratives of moral appeasement and civic conscience that help citizens evaluate political leaders. This research focuses on how narratives about the moral legitimacy of local democracy can affect civic trust in and support for electoral legitimacy. Employing a qualitative case study method in the City of Cirebon, West Java, this study centers on a legislative candidate whose electoral legitimacy was largely based on moral and religio-moral transformation narratives. Data were collected through in-depth interviews with seven informants selected purposively, including the elected legislative candidate himself, one leader of the candidate’s campaign team, and five ordinary people from the community who had exposure to the candidate’s social engagement program. The results of this research show that civic trust was produced less by vote-buying or material incentive appeals and programmatic appeals but more by the notions of morality associated with consistency, social accessibility, and persistent programs for local citizens. Moral narratives were symbolic resources to shore up public trust and gain electoral legitimacy. The study concludes that electoral legitimacy in local democracy is socially constructed through the interaction between moral narratives, relational trust, and everyday community networks.